Surgical intervention of a nonunion navicular stress fracture in a collegiate soccer Player: an exploration clinical case report - DelBusso, S.; Matheny, M. (International Journal of Athletic Therapy & Training, 2019)
The following case presents an 18-year-old male collegiate soccer player 11 months after initial injury, who was previously diagnosed with and treated for a navicular stress fracture. Unlike most patients who are treated conservatively, he presented with lingering symptoms that had not resolved after the standard course of treatment. After 11 months, the athlete then underwent further testing to reveal a navicular stress fracture with nonunion due to avascular necrosis. Open reduction internal fixation was performed 17 months after the initial injury to stabilize the midfoot. This case presents many unique components, including the presentation of the injury, the unsuccessful course of initial treatment, and the complications that arose from it.